2016
DOI: 10.1371/journal.pone.0165764
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Expression Profiling of miRNAome in Goat longissimus dorsi Muscle from Prenatal Stages to a Neonatal Stage

Abstract: Skeletal muscle development is a complex biological process regulated by numerous genes and non-coding RNAs, such as microRNAs (miRNAs). In the current study, we made use of the deep sequencing data from Jianzhou Da’er goat longissimus dorsi sampled on days 45, 60, and 105 of gestation, as well as day three after birth to identify miRNAs that regulate goat skeletal myogenesis, and examine their temporal expression profiles. A total of 410 known goat miRNAs, 752 miRNA homologs and 88 novel miRNAs were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 54 publications
2
24
0
1
Order By: Relevance
“…Since muscle development was accompanied by the differential expression of related genes in different growth periods and our data were also collected at different time points, we used STEM software, which is widely used to study dynamic biological processes (Guo et al, 2016;Ma et al, 2018;Zhan et al, 2018), to investigate the dynamic genetic changes during breast muscle development. We experimented with various numbers of profiles and found that five profiles (combining with three clusters) best captured the expression patterns of DEGs (Figure 2 and Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…Since muscle development was accompanied by the differential expression of related genes in different growth periods and our data were also collected at different time points, we used STEM software, which is widely used to study dynamic biological processes (Guo et al, 2016;Ma et al, 2018;Zhan et al, 2018), to investigate the dynamic genetic changes during breast muscle development. We experimented with various numbers of profiles and found that five profiles (combining with three clusters) best captured the expression patterns of DEGs (Figure 2 and Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of miR3405p is known to reduce the expression of Nrf2 protein in the postexercise skeletal muscle of mice [83]. miR-424 and miR-542-3p are among the most abundant miRNAs in goat muscles [20]. Meanwhile, Garros et al stated that miR-542 overexpression caused muscle wasting in mice, and reduced mitochondrial function [84].…”
Section: Discussionmentioning
confidence: 99%
“…Except for linear transcripts like miRNA, lncRNAs, and mRNAs, numerous circular RNAs (circRNAs) responsible for skeletal muscle development have been identi ed through the introduction of high throughput sequencing technology [19][20][21]. circRNAs are newly discovered non-coding RNA molecules with a closed-loop structure and acting as gene regulators in most organisms [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The clean reads were aligned with Silva, GtRNAdb, Rfam, and Repbase databases, respectively, to filter rRNA, tRNA, snRNA, snoRNA, other ncRNA, and repeat sequences using the Bowtie v.1.1.0 software ( Langmead et al, 2009 ). The derived reads were used to detect known goat miRNAs by aligned to the goat miRNA precursors present in the miRBase v21 2 as described in our previous study ( Guo et al, 2016a ). Clear reads were also mapped to the goat reference genome (CHIR_1.0, NCBI) using the Bowtie aligner.…”
Section: Methodsmentioning
confidence: 99%